Prevalence and associated factors of perinatal depression among working pregnant women: a hospital-based cross-sectional study. Issue 1 (31st December 2022) - Jihed, Abdallah; Ben Rejeb, Mohamed; Said Laatiri, Houyem; Zedini, Chekib; Mallouli, Manel; Mtiraoui, Ali
ABSTRACT: Perinatal depression is a major public health problem having serious negative impacts on personal, family, and child developmental outcomes. This study aimed to determine the prevalence of major depressive disorder (MDD) and its associated factors in working pregnant women. This descriptive, cross-sectional study was performed on 389 working pregnant women enrolled from four Tunisian public maternity hospitals. Data collection tools were the sociodemographic, obstetric, family relationships, and work environment questionnaire, and the Center for Epidemiologic Studies Depression Scale (CES-D). The mean score of depression was 27.39 ± 6.97 and 76.1% of women had major depressive symptoms using cutoff points on the CES-D ≥ 23. Family income, diagnosis with a chronic illness, history of depression, and employment categories were associated with major depressive symptoms. In multivariate analyses, family income and work posture were significantly associated with MDD. These results suggest an increased burden of MDD during pregnancy in Tunisian women. Prevention, early detection, and interventions are needed to reduce the prevalence of perinatal depression.